Loss of muscle mass: current developments in cachexia and sarcopenia focused on biomarkers and treatment. Issue 4 (December 2015) - Drescher, Cathleen; Konishi, Masaaki; Ebner, Nicole; Springer, Jochen
Abstract: Loss of muscle mass arises from an imbalance of protein synthesis and protein degradation. Potential triggers of muscle wasting and function are immobilization, loss of appetite, dystrophies, and chronic diseases as well as aging. All these conditions lead to increased morbidity and mortality in patients, which makes it a timely matter to find new biomarkers to get a fast clinical diagnosis and to develop new therapies. This mini‐review covers current developments in the field of biomarkers and drugs on cachexia and sarcopenia. Here, we reported about promising markers, e.g. tartate‐resistant acid phosphatase 5a, and novel substances like epigallocatechin‐3‐gallate. In summary, the progress to combat muscle wasting is in full swing, and perhaps diagnosis of muscle atrophy and of course patient treatments could be soon support by improved and more helpful strategies.